Methods of pain control during endometrial biopsy: A systematic review and meta-analysis of randomized controlled trials - Kittipat Charoenkwan (2020)
© 2019 Japan Society of Obstetrics and Gynecology Aim: To review effectiveness of methods for reducing pain during endometrial biopsy. Methods: PubMed, Scopus, Cochrane Central Register of Controlled Trials and ClinicalTrials.gov databases were searched for randomized controlled trials that examined effectiveness of pain control methods for endometrial biopsy. Risk of bias was assessed from sequence generation, allocation concealment, blinding, incomplete outcome data and selective outcome reporting. Heterogeneity was examined from forest plot, statistical tests of homogeneity, and I2 statistic. For meta-analysis of pain scores, weighted mean difference with 95% confidence interval (CI) were estimated. Results: Twenty-six studies were included in the review. Marginally significant reduction in the pain score during the procedure in participants with intrauterine lidocaine relative to control was observed (mean difference [MD] −1.31, 95% confidence interval [CI] −2.70 to 0.09, P = 0.07). Subgroup analysis showed that in studies that used low-pressure suction devices, intrauterine lidocaine was associated with statistically significant reduction in pain during the procedure (MD −2.22, 95% CI −3.72 to −0.73, P = 0.004). There was a significantly lower pain score during biopsy in the anesthetic spray group compared to control (MD −0.96, 95% CI −1.53 to −0.39, P = 0.001). Significant heterogeneity on types of intervention and outcome measures among studies that examined paracervical block and nonsteroidal anti-inflammatory drugs (NSAID) was observed. However, paracervical block and NSAID were associated with significant pain reduction compared to placebo in most of the related studies. Conclusion: Intrauterine anesthetics, anesthetic cervical spray, paracervical block and oral NSAID provide effective pain control during endometrial biopsy.